2019
DOI: 10.3390/foods8030101
|View full text |Cite
|
Sign up to set email alerts
|

Validation Including Uncertainty Estimation of a GC–MS/MS Method for Determination of Selected Halogenated Priority Substances in Fish Using Rapid and Efficient Lipid Removing Sample Preparation

Abstract: A rapid method is proposed for the determination of selected H2SO4 stable organic compounds—eight organochlorines (OCs; hexachloro-1,3-butadiene, pentachlorobenzene, hexachlorobenzene, hexachlorocyclohexane—HCH—isomers, heptachlor) and six polybrominated diphenyl ethers (PBDEs; BDE-28, 47, 99, 100, 153, 154)—in fish samples. In the method, a modified QuEChERS (quick, easy, cheap, effective, rugged and safe) sample preparation using pH-tuned dispersive liquid–liquid microextraction (DLLME) and H2SO4 digestion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…ME values were between −9% and −212% for OCPs, 1% and 29% for OPPs, 3% and −174% for BFRs, −16% and −107% for PCBs and 38% and 61% for SMs ( Table S5 ). For all the compounds analyzed, 49.0% of the analytes suffered ion suppression, 21.6% ion enhancement and 29.4% were in the range of −20–20%, not considered the ME [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ME values were between −9% and −212% for OCPs, 1% and 29% for OPPs, 3% and −174% for BFRs, −16% and −107% for PCBs and 38% and 61% for SMs ( Table S5 ). For all the compounds analyzed, 49.0% of the analytes suffered ion suppression, 21.6% ion enhancement and 29.4% were in the range of −20–20%, not considered the ME [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The recoveries for shrimp samples were calculated using spiked samples at three levels, 16, 24 and 32 ng/g w / w for OCPs, 16, 28 and 40 ng/g w / w for OPPs and 8, 14 and 20 ng/g w / w for BFRs, PCBs and SMs, with each level in triplicate. The ME was calculated, as previously described [ 32 ], using standard solutions prepared in n-hexane compared to spiked blank samples. A positive result corresponds to an enhancement of the analytical response, whereas a negative value corresponds to a suppression effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Static headspace gas chromatography mass spectrometry (SHS-GC-MS) is a powerful and efficient way to profile the composition of complex volatile components due to its effectiveness in simultaneous chromatographic separation and structural identification [21,22]. Compared to direct injection, SHS sampling is clean and convenient as a gas extraction technique for GC-MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of these pre-treatment assays for sample preparation is based on the QuEChERS method, with the advantages summarized in its acronym (quick, easy, cheap, effective, rugged, and safe). The study of Nagyová and Tölgyessy [5] reported the validation of a rapid and non-laborious method for the determination of selected H 2 SO 4 stable halogenated priority pollutants (eight organochlorines and six polybrominated diphenyl ethers) in nine different fish species. A modified QuEChERS sample preparation followed by gas chromatography-triple quadrupole tandem mass spectrometry analysis was described.…”
mentioning
confidence: 99%